Advocate Immunity Rights in Providing Legal Services to Clients - Yohanes Pande; Zakiyatun Nufus; Patawari Patawari; Rica Gusmarani; Muchamad Taufiq (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
An advocate is a person whose profession is to provide legal services, both inside and outside the court, who fulfill the requirements under the Advocate law. Advocates are law enforcers, free and independent, guaranteed by laws and regulations." In this way, it has been clearly stated that the position of advocates is equal to that of police, prosecutors and judges as law enforcers. In providing legal aid services to their clients, advocates have the right to immunity and cannot be sued either civilly or criminally, as regulated in Article 16 of Law Number 18 of 2003 concerning Advocates and strengthened by the decision of the Constitutional Court (MK) which states that the right to immunity This applies both inside and outside the court. An advocate's immunity is always limited by good faith, which is defined in the Elucidation to Article 16 of the Advocate Law, namely that what is meant by good faith is carrying out professional duties for the sake of upholding justice based on the law to defend the interests of clients.